Patients’ and caregivers’ perceptions of bariatric surgery: A France and United States comparative infodemiology study using social media data mining - Czernichow, Sébastien; Rassy, Nathalie; Malaab, Joelle; Loussikian, Paul; Mebarki, Adel; Khadhar, Mickail; Poghosyan, Tigran; Fagherrazi, Guy; Carette, Claire; Schück, Stéphane; Rives-Lange, Claire (Frontiers in Digital Health, 2023)
Background: People are conversing about bariatric surgery on social media, but little is known about the main themes being discussed. Objective: To analyze discussions regarding bariatric surgery on social media platforms and to establish a cross-cultural comparison of posts geolocated in France and the United States. Methods: Posts were retrieved between January 2015 and April 2021 from general, publicly accessed sites and health-related forums geolocated in both countries. After processing and cleaning the data, posts of patients and caregivers about bariatric surgery were identified using a supervised machine learning algorithm. Results: The analysis dataset contained a total of 10 800 posts from 4 947 web users in France and 51 804 posts from 40 278 web users in the United States. In France, post-operative follow-up (n=3251, 30.1% of posts), healthcare pathways (n=2171, 20.1% of the posts), and complementary and alternative weight loss therapies (n=1652, 15.3% of the posts) were among the most discussed topics. In the United States, the experience with bariatric surgery (n=11 138, 21.5% of the posts) and the role of physical activity and diet in weight-loss programs before surgery (n=9 325, 18% of the posts) were among the most discussed topics. Conclusions: Social media analysis provides a valuable toolset for clinicians to help them increase patient-centered care by integrating the patients' and caregivers' needs and concerns into the management of bariatric surgery.